Retrospective observational study of asthma and chronic obstructive pulmonary disease prevalence and associated healthcare resource utilization in a large, integrated healthcare system. Issue 6 (2nd November 2022) - Collinsworth, Ashley W.; Masica, Andrew L.; Kudyakov, Rustam; Bayer, Valentina; Millard, Mark W.; Shaikh, Asif
Abstract: Limited data exist on asthma and chronic obstructive pulmonary disease (COPD) management—major drivers of healthcare resource utilization (HCRU) in the USA. We describe prevalence and exacerbation rates, therapeutic interventions, and HCRU for asthma and/or COPD within a large, integrated healthcare system. Patients with asthma, COPD, and asthma + COPD were identified from retrospective electronic health record data (2016–2018) of >1.7 million patients. Descriptive analysis of disease prevalence and exacerbation frequencies, pharmacotherapies, and HCRU was performed. Time-to-event analysis of time to first exacerbation was performed in patients with asthma and/or COPD. Exacerbation rates, pharmacotherapies, and HCRU were examined by exploratory analysis in an outpatient subset. Overall, 149, 086 unique patients (8.6%) had encounters for asthma, COPD, or asthma + COPD. Acute care utilization was high, including emergency department visits (asthma, 52.9%; COPD, 35.1%) and hospitalizations (asthma, 26.7%; COPD, 65.7%). Many patients were prescribed short-acting therapies (asthma, 45.3%; COPD, 40.0%; asthma + COPD, 54.7%). Prescription rates for maintenance therapies were low (17.1%, 20.8%, 31.7%) and annual exacerbation rates were 0.65, 0.80, and 1.33. This analysis showed a substantive prevalence of pulmonary disease, variability between documented prescriptions and pharmacotherapy guidelines, and high HCRU. Appropriate tailoring of pharmacotherapies and management of asthma and COPD over a continuum are opportunities to improve patient care.